First Case of Bacteraemia Due to Carbapenem-Resistant Bacteroides faecis - Charlotte Kaeuffer; Tiffany Ruge; Laure Diancourt; Benoît Romain; Yvon Ruch; Benoît Jaulhac; Pierre H. Boyer (Antibiotics, 2021)
Multidrug resistant (MDR) bacteria are increasingly observed in nosocomial and community-acquired settings. Anaerobes are no exception to this rule, but there are fewer reports of MDR in the scientific literature on anaerobes than there are for other bacteria. In this short case report, we describe the first case of bacteraemia caused by a multidrug-resistant Bacteroides faecis, which produces a carbapenemase encoded by the blaCfiA gene. This bacteraemia followed a digestive surgery operation. Surprisingly, these findings did not lead to a change in antibiotic therapy, probably because the patient’s clinical state had improved. Nevertheless this report calls for better knowledge of anaerobic bacteria and for a systematic antimicrobial stewardship procedure following bacteraemia.